Comprehensive data validation of a combined weekly time use and travel survey. (November 2021) - Aschauer, Florian; Hössinger, Reinhard; Jara-Diaz, Sergio; Schmid, Basil; Axhausen, Kay; Gerike, Regine
Highlights: Immediate follow-up data completion (validation) minimizes item-nonresponse errors. Effects of validation are analysed for a sample of travel behaviour and time use data. Incorrectly reported and completely non-reported trips and activities are described. The effort for validation (time of work hours respectively money) accounted for 12 percent of the overall fieldwork effort. Abstract: A well-known problem in Household Travel Surveys (HTS) is item-nonresponse, which occurs when complete trips are not reported or only partial information for trips is given. This article presents a comprehensive data validation effort (data completion and correction through immediate call-backs of the survey participants) on travel and non-travel information as part of a one-week Mobility-Activity-Expenditure Diary Survey. Validation recovered 2.5 percent reporting days of mobile persons with complete information on trips and increased the number of trips of pre-existing mobile reporting days by 3.5 percent. The characteristics of these trips confirm and extend the findings from item-nonresponse studies without validation: The majority of the new trips begin in the afternoon; they are mainly short and irregular; the most important trip purposes are home, work, shopping, and leisure. 37 percent of the new trips generated completely new tours; females seem to under-report less than men do. The analysis of the information on the time use (activities) between trips showed that the data was recorded with high accuracy and completeness even before validation. This study confirms typical item-nonresponse patterns and provides a solution for their mitigation through direct follow-up validation. The validation effort increased the time and cost of fieldwork by 12 percent.